An Endophytic Fungus, Talaromyces radicus, Isolated from Catharanthus roseus, Produces Vincristine and Vinblastine, Which Induce Apoptotic Cell Death - Palem, Padmini P. C.; Kuriakose, Gini C.; Jayabaskaran, Chelliah (PLOS ONE, 2015)
Endophytic fungi isolated from Catharanthus roseus were screened for the production of vincristine and vinblastine. Twenty-two endophytic fungi isolated from various tissues of C. roseus were characterized taxonomically by sequence analysis of the internal transcribed spacer (ITS) region of rDNA and grouped into 10 genera: Alternaria, Aspergillus, Chaetomium, Colletotrichum, Dothideomycetes, Eutypella, Eutypa, Flavodon, Fusarium and Talaromyces. The antiproliferative activity of these fungi was assayed in HeLa cells using the MTT assay. The fungal isolates Eutypella sp—CrP14, obtained from stem tissues, and Talaromyces radicus—CrP20, obtained from leaf tissues, showed the strongest antiproliferative activity, with IC50 values of 13.5 μg/ml and 20 μg/ml, respectively. All 22 endophytic fungi were screened for the presence of the gene encoding tryptophan decarboxylase (TDC), the key enzyme in the terpenoid indole alkaloid biosynthetic pathway, though this gene could only be amplified from T. radicus—CrP20 (NCBI GenBank accession number KC920846). The production of vincristine and vinblastine by T. radicus—CrP20 was confirmed and optimized in nine different liquid media. Good yields of vincristine (670 μg/l) in modified M2 medium and of vinblastine (70 μg/l) in potato dextrose broth medium were obtained. The cytotoxic activity of partially purified fungal vincristine was evaluated in different human cancer cell lines, with HeLa cells showing maximum susceptibility. The apoptosis-inducing activity of vincristine derived from this fungus was established through cell cycle analysis, loss of mitochondrial membrane potential and DNA fragmentation patterns.